2019
DOI: 10.1130/ges02040.1
|View full text |Cite
|
Sign up to set email alerts
|

Deformation conditions during syn-convergent extension along the Cordillera Blanca shear zone, Peru

Abstract: Strain localization across the brittle-ductile transition is a fundamental process in accommodating tectonic movement in the mid-crust. The tectonically active Cordillera Blanca shear zone (CBSZ), a ∼200-km-long normal-sense shear zone situated within the footwall of a discrete syn-convergent extensional fault in the Peruvian Andes, is an excellent field laboratory to explore this transition. Field and microscopic observations indicate consistent top-down-to-the-southwest sense of shear and a sequence of tecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 145 publications
(250 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, the calculated depths are consistent with the two styles of faulting in the area. The Cordillera Blanca detachment system is extensional with penetration depths at least 10 km (Giovanni et al, 2010; Hughes et al, 2019; McNulty & Farber, 2002). In contrast, most of the MFTB structures are more shallowly penetrating and sole out into décollements within 5 km (e.g., Scherrenberg et al, 2016), consistent with thin‐skinned fold and thrust belt deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the calculated depths are consistent with the two styles of faulting in the area. The Cordillera Blanca detachment system is extensional with penetration depths at least 10 km (Giovanni et al, 2010; Hughes et al, 2019; McNulty & Farber, 2002). In contrast, most of the MFTB structures are more shallowly penetrating and sole out into décollements within 5 km (e.g., Scherrenberg et al, 2016), consistent with thin‐skinned fold and thrust belt deformation.…”
Section: Discussionmentioning
confidence: 99%
“…The detachment is well exposed near the mouth of glacially cut valleys (quebradas) along the western slopes of the Cordillera Blanca. North of Huaraz, the structure is characterized by an extensional shear zone with a gradient from mylonitic fabrics to brittle overprinting toward to the detachment surface (Giovanni et al, 2010; Hughes et al, 2019). South of Huaraz the mylonitic zones are rare to absent, and the fault breaks into segments, terminating ~80 km to the SE (Figure 1).…”
Section: Geological Settingmentioning
confidence: 99%
“…We do not use naturally constrained strain rate and deformation data from the RGD (Dunlap et al., 1997; Hirth et al., 2001), the Ailao Shan–Red River shear zone (ARSZ; Boutonnet et al., 2013; Sassier et al., 2009), nor the Cordillera Blanca shear zone (CBSZ; Hughes et al., 2019, 2020). In the RGD, Hirth et al.…”
Section: Methodsmentioning
confidence: 99%
“…We do not use naturally constrained strain rate and deformation data from the RGD (Dunlap et al, 1997;Hirth et al, 2001), the Ailao Shan-Red River shear zone (ARSZ; Boutonnet et al, 2013;Sassier et al, 2009), nor the Cordillera Blanca shear zone (CBSZ; Hughes et al, 2019Hughes et al, , 2020. In the RGD, Hirth et al (2001) constrained strain rates within ∼1.5 orders of magnitude (1 × 10 −15 to 5 × 10 −14 s −1 ) and the differential stress to between 60 and 100 MPa (although dynamically recrystallized grain sizes reported by Dunlap et al (1997) suggest that lower stresses were present).…”
Section: Selection Of Natural Datamentioning
confidence: 99%
“…Others have suggested that the meteoric water in shear zones originates from unconformities or is brought to depth during polyphase deformation prior to shear zone formation (Raimondo et al, 2013;Bons and Gomez-Rivas, 2020). The granite forming the CBD footwall was intruded before and up to fault initiation, and the system has a monophasic deformation and exhumation history that precludes these mechanisms as the origin of low-δ 2 H fluids (Margirier et al, 2016;Hughes et al, 2019). Additionally, an active meteorichydrothermal system permits circulation of groundwater along the CBD and bedrock fractures to depths of 9-11 km ( Newell et al, 2015;Scott et al, 2020).…”
Section: Introductionmentioning
confidence: 99%